Pengaruh Pandemi COVID-19 dan Trading Activities terhadap Return Saham - Widyasari, Kezia Dayu Prasasti, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to determine the effect of COVID-19 pandemic and trading activities on stock market return in healthcare companies and transportation & logistic companies that was listed in Indonesia Stock Exchange during the research period. The study period from March 2, 2020 to December 31, 2020. The research finds that the best model used in predicting stock market returns is random effect model compared to other 2 selected models. Variables related to COVID-19 outbreak which are daily growth in confirmed cases and daily growth in death causes by COVID-19 were found not affect the stock market return significantly. However, this study found that trading activities described by trading volume and trading frequency variables during the research period had positive and significant effect to the stock market returns.